2021
DOI: 10.1371/journal.pone.0248713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of 952 hospitalized COVID-19 patients in The Netherlands: A retrospective cohort study

Abstract: Objective To describe clinical characteristics, disease course and outcomes in a large and well-documented cohort of hospitalized COVID-19 patients in the Netherlands. Methods We conducted a multicentre retrospective cohort study in The Netherlands including 952 of 1183 consecutively hospitalized patients that were admitted to participating hospitals between March 2nd, 2020, and May 22nd, 2020. Clinical characteristics and laboratory parameters upon admission and during hospitalization were collected until J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 29 publications
9
37
3
3
Order By: Relevance
“…Overall, in our study population, the COVID-19 patients with an ICU stay showed more clinical signs of severe disease: higher inflammatory blood markers at admission (CRP, white blood cell count and ferritin), higher rate of fever at admission and higher oxygen need, which resulted in higher mortality as compared to patients solely admitted to the COVID-19 ward. This is in line with several observational COVID-19 studies [ 23 , 24 ]. At least one respiratory sample was available in no more than 29% of the admissions (18% forward admissions, 58% for ICU admissions).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, in our study population, the COVID-19 patients with an ICU stay showed more clinical signs of severe disease: higher inflammatory blood markers at admission (CRP, white blood cell count and ferritin), higher rate of fever at admission and higher oxygen need, which resulted in higher mortality as compared to patients solely admitted to the COVID-19 ward. This is in line with several observational COVID-19 studies [ 23 , 24 ]. At least one respiratory sample was available in no more than 29% of the admissions (18% forward admissions, 58% for ICU admissions).…”
Section: Discussionsupporting
confidence: 92%
“…The crude mortality rate in our study population of inpatients during the first year of the pandemic was 19.4%, within the range of other studies reporting rates of 4–28%, although generally other studies have had smaller populations ( 14 ), especially with regard to those admitted to the ICU ( 15 , 16 ). In our study, the median interval from onset to admission, not counting those with nosocomial infections, was slightly shorter at 4.6 days than the 7-day interval reported in a retrospective multicenter cohort study from the Netherlands ( 17 ), which may reflect a faster and more severe evolution in our patients. Unlike other studies ( 18 ), we did not find a higher risk in men after adjusting for comorbidity and age.…”
Section: Discussioncontrasting
confidence: 71%
“…Notwithstanding remdesivir use, these clinical characteristics are consistent with those of hospitalized COVID-19 patients; in this regard, in fact, regardless the therapeutic strategy, several studies have tried to identify clinical and demographic characteristics, as well as potential factors of worst outcomes, associated to hospitalized COVID-19 patients. Through a retrospective cohort study, Pouw N and collaborators found that a median age of 69 years and the male gender were the prevalent demographic features of hospitalized COVID-19 patients in the Netherlands [ 12 ]. Moreover, Gavin W also concluded that an older age and being male may worsen outcomes in COVID-19 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%